Managing supraventricular tachyarrhythmia in pregnant patients within the emergency department - Pan, Di; Chen, Zhongqing; Chen, Haibo (Frontiers in Cardiovascular Medicine, 2024)
BackgroundPregnancy increases the risk of supraventricular tachycardia (SVT) due to physiological changes. This study reviews the management of SVT in pregnant patients in the emergency department (ED).MethodsWe retrospectively analyzed 15 pregnant patients with SVT treated at Shenzhen Second People's Hospital ED from 2015 to 2023. Treatments included vagal nerve stimulation, pharmacotherapy, esophageal pacing, cardioversion, and radiofrequency ablation.ResultsThe average patient age was 30.3 years. All presented with palpitations, and none had hemodynamic instability. Treatment success varied: 3 patients reverted spontaneously, 5 responded to vagal stimulation, and 4 to esophageal pacing. One required verapamil, and another responded to labetalol after failing vagal and pacing treatments.ConclusionWhen managing SVT during pregnancy, it is important to consider the patient's stability, the stage of pregnancy, and the safety of medications. For unstable patients, electrical cardioversion is the preferred option; for stable patients, vagus nerve stimulation (VNS) or other alternative treatments, such as adenosine, should be considered.